Disentangling the relative contributions of atmospheric demand for water and soil water availability on the stomatal limitation of photosynthesis - Lavergne,A; Graven,H; Prentice,IC (2020)
Plants open and close their stomata in response to changes in the environment, so they can absorb the CO2 they need to grow, while also avoid drying out. Since the activities of leaf stomata determine the exchanges of carbon and water between the vegetation and the atmosphere, it is crucial to incorporate their responses to environmental pressure into the vegetation models predicting carbon and water fluxes on broad spatial and temporal scales. The least-cost optimality theory proposes a simple way to predict leaf behaviour, in particular changes in the ratio of leaf internal (ci) to ambient (ca) partial pressure of CO2, from four environmental variables, i.e. ca, growing-season temperature (Tg), atmospheric vapour pressure deficit (Dg), and atmospheric pressure (as indexed by elevation, z). However, even though the theory considers the effect of atmospheric demand for water on ci/ca, it does not predict how dry soils with reduced soil water availability further influence c</em&